Consensus paper: current state of first- and second-line therapy in advanced clear-cell renal cell carcinoma - Goebell, Peter; Ivanyi, Philipp; Bedke, Jens; Bergmann, Lothar; Berthold, Dominik; Boegemann, Martin; Busch, Jonas; Doehn, Christian; Krege, Susanne; Retz, Margitta; Amsberg, Gunhild Von; Grimm, Marc-Oliver; et al. (Future Oncology, 2020)
The therapy of advanced (clear-cell) renal cell carcinoma (RCC) has recently experienced tremendous changes. Several new treatments have been developed, with PD-1 immune-checkpoint inhibition being the backbone of therapy. Diverse immunotherapy combinations change current first-line standards. These changes also require new approaches in subsequent lines of therapy. In an expert panel, we discussed the new treatment options and how they change clinical practice. While first-line immunotherapies introduce a new level of response rates, data on second-line therapies remains poor. This scenario poses a challenge for clinicians as guideline recommendations are based on historical patient cohorts and agents may lack the appropriate label for their in guidelines recommended use. Here, we summarize relevant clinical data and consider appropriate treatment strategies.
CRIS-Team WoS Importer:2020-10-09